Evolution of Mining-Induced Stress in Downward Mining of Short-Distance Multiseam. (4th March 2022) - Yang, Ke; Fu, Qiang; Liu, Qinjie; He, Xiang; Lyu, Xin
Abstract : The strong disturbance of upward mining of the short-distance multiseam results in frequent fractures in the coal seam to be mined, jeopardizing the operation safety due to the instability of the surrounding rock of the overlying stope and risks of coal and gas outburst. A lucrative alternative is the downward mining of multiseam, which wide implementation is limited by the lack of reliable data on stress evolution characteristics. In this paper, the evolution, nonlinear interaction, and superposition characteristics of mining-induced stress after multiple pressure relief in the short-distance multi-seam were investigated by the numerical simulation and physical simulation, taking the endowment and mining technology characteristics of group B short-distance multiseam in Pan'er Coal Mine in Anhui Province of China as an example. The numerical and physical models of multiple (2—5 times) mining activities in pressure relief multiseam (with five main coal layers) under downward mining are constructed and implemented with the FLAC3D software and 1 : 100 scaling, respectively. The results showed that a pressure relief arch, which bears and transfers stresses, is formed on the coal seam's roof and floor. In downward mining, the local arch expands to the long arch, which bearing capacity within the influence range of multiple mining disturbances is weak, and the arch structure is prone to instability. If a coal pillar is left in the upper coal seam after its mining, the lower coal seam mining will switch from the large-scale low-stress area under the goaf to the small-scale high-stress area of nonlinear interaction of the multiple mining stresses with the stress under the coal pillar.